Spinal Injections - Gimarc, David C.; Stratchko, Lindsay M.; Ho, Corey K. (Seminars in Musculoskeletal Radiology, 2021)
Spinal pain is a common complaint and cause of disability in the United States, affecting most individuals at some point in their lives. The complex anatomy of the spine leads to multiple potential and coexisting etiologies for pain, and the differentiation of these sources can present a diagnostic challenge. Image-guided spinal injections can provide both diagnostic information identifying pain location as well as prolonged therapeutic relief as an alternative to medical management. Anesthetic and corticosteroid medications can be administered within the epidural space through transforaminal or interlaminar approaches, blocking various sensory nerves, or directly within the facet joints. Proceduralists must be aware of associated patient considerations, techniques, and potential complications to perform the procedures safely. We discuss image-guided spinal injection techniques, based on best practices and our experiences.
Keywords: spine; pain; injection; epidural; intervention